Multidrug-Resistant Acinetobacter baumannii: Risk Factors for Mortality in a Tertiary Care Teaching Hospital - Kristina Černiauskienė; Astra Vitkauskienė (Tropical Medicine and Infectious Disease)
Background and objectives: Due to resistance and the lack of treatment options, hospital-acquired Acinetobacter baumannii (A. baumannii) infections are associated with high mortality. This study aimed to analyze the characteristics of patients with infections caused by multidrug-resistant (MDR) A. baumannii and patients’ clinical outcomes as well as determine the risk factors for mortality in a tertiary care teaching hospital. Materials and methods: A retrospective cohort study including 196 adult patients with A. baumannii strains isolated from different clinical specimens in the Hospital of the Lithuanian University of Health Sciences in 2016, 2017, 2020, and 2021 was conducted. Data on patients’ characteristics, comorbid diseases, treatment, length of hospital and ICU stay, and outcome were collected. Carbapenemase-producing isolates were detected phenotypically. To determine risk factors for in-hospital mortality, logistic regression analysis was performed. Results: There were 60 (30.6%) women and 136 (69.4%) men with a mean age of 61.7 ± 16.6 years (range, 52–74). More than three-fourths (76.5%, n = 150) of the patients had at least one comorbid disease. The highest number of A. baumannii strains were isolated from patients hospitalized in ICUs (43.4%, n = 85). A. baumannii strains producing three types of β-lactamases were more frequently isolated from women than men (77.8% vs. 22.2%, p = 0.006). Infections caused by A. baumannii strains producing two types of β-lactamases were significantly more often treated with combination therapy than infections caused by strains producing one type of β-lactamase (78.9% vs. 60.0%, p = 0.019). Patients with A. baumannii strains producing two different types of β-lactamases (AmpC plus KPC, AmpC plus ESBL, or ESBL plus KPC) stayed significantly shorter at the ICU compared to patients with A. baumannii strains with no detected β-lactamases (median of 9, IQR 2–18, vs. median of 26, IQR 7–38, p = 0.022). Death occurred in 58.7% (n = 115) of patients. Logistic regression analysis showed that a duration of the effective antibiotic treatment of ≤6 days, invasive mechanical ventilation, combination therapy, aged >58 years, and the absence of co-infection were independent predictors of in-hospital mortality. Conclusions: MDR A. baumannii infections pose a significant threat to human health not only due to multidrug resistance but also due to high mortality. The mortality rate of patients with MDR A. baumannii infection was high and was associated with age, invasive mechanical ventilation, the duration of effective antibiotic treatment, no co-infection, and combination therapy. Therefore, it is of utmost importance to reduce the prevalence of MDR A. baumannii infections in healthcare facilities by applying preventive measures and to administer timely effective treatment once A. baumannii infection is detected.